A novel detection method applied on low-frequency harmonics of Tokamak power supply - Yunxiang Tian (Elsevier, 2021)
Non-characteristic low-frequency harmonics generated by non-linear devices have properties of small amplitude and non-stationary state, and contain complex side-lobe inter-harmonics, which is difficult to achieve the precise and real-time extraction for continuous inter-spectral harmonics. Aiming at the problem, a novel method for detection based on cosine bandpass FIR (CBP-FIR) filter with fixed central frequency and faster operation speed is introduced. Considering the actual working condition, the improved cosine bandpass FIR (ICBP-FIR) filter is proposed, which can flexibly adjust the central frequency and phase range. ICBP-FIR filter has excellent harmonic detection precision, system stability margin and dynamic robustness characteristics for both inter-harmonics and integer harmonics. Analysis with MATLAB is adopted to improve the design process. The validity of ICBP-FIR algorithm is verified by experiments based on Digital Signal Processing (DSP).